Exploring Community Stakeholders’ Perceptions of the Enhancing Family Well-being Project in Hong Kong: A Qualitative Study - Chu, Joanna T. W.; Chan, Sophia S.; Stewart, Sunita M.; Zhou, Qianling; Leung, Charles Sai-Cheong; Wan, Alice; Lam, Tai Hing (Frontiers in Public Health, 2017)
Background: Community engagement is a powerful tool in bringing about positive social and community change. Community stakeholders possess critical experience and knowledge that are needed to inform the development of community-based projects. However, limited literature is available on the practical experience involved with planning and implementing community-based family programs. Even less has been published documenting efforts in Chinese communities. This paper explores community stakeholders’ experiences with the Enhancing Family Wellbeing Project - part of a citywide project entitled the “FAMILY Project”, aimed at promoting family health, happiness, and harmony in Hong Kong. Methods: This qualitative evaluation examined the perspectives of community stakeholders. Four focus groups with social workers (n = 24) and six in-depth interviews with steering committee members were conducted from December 2012 to May 2013 in Hong Kong. Focus groups and in-depths interview were audiotaped, transcribed and analyzed using thematic analysis techniques. Results: Rich accounts were given by our respondents on various aspects of the project. Main themes and subthemes were identified and grouped into four categories (project conception, project implementation, project consolidation, and the overall impact of the project). Respondents described the practical challenges associated with the project (e.g., recruitment, balancing scientific research, and lack of resources) and identified the elements that are important to the success of the project. These included the commitment to a shared goal, multi-agency collaboration, and a platform for knowledge exchange. Finally, respondents perceived benefits of the project at both the individual and community level. Conclusion: Our project sheds light on many of the practical considerations and challenges associated with a designing and implementing a community-based family intervention project. Community stakeholders input provided important information on their perceived benefits and barriers, and can inform and improve future development of community-based family intervention programs. Keywords: qualitative, community engagement, community stakeholders, community-based interventions, family intervention